VerifyThis – Verification Competition with a Human Factor - Ernst, Gidon; Huisman, Marieke; Mostowski, Wojciech; Ulbrich, Mattias (Lecture Notes in Computer Science, 2019)
VerifyThis is a series of competitions that aims to evaluatethe current state of deductive tools to prove functional correctness of programs. Such proofs typically require human creativity, and hence iti s not possible to measure the performance of tools independently of the skills of its user. Similarly, solutions can be judged by humans only. Inthis paper, we discuss the role of the human in the competition setup and explore possible future changes to the current format. Regarding the impact of VerifyThis on deductive verification research, a survey conducted among the previous participants shows that the event is a key enabler for gaining insight into other approaches, and that it fosters collaboration and exchange. © 2019, The Author(s).